A Methodological Approach to Historic Building Conservation: A DSS for Restoration Project Process Optimisation - Okar, Eren; Demir, Yüksel (İstanbul Üniversitesi, 2025)
This study investigates ongoing project submission and evaluation processes in institutions responsible for restoration projects in Turkey to accelerate processes by digitising and transferring restoration project submission and evaluation processes to a digital environment for sustainable conservation and to ensure resilient archives. The proposed method is based on domain knowledge acquisition and content analysis of multiple interviews. The study hypothesised that a decision support system (DSS) would be suitable for digitalising the process because both systems perform on flowcharts. The interviews were conducted based on content analyses of multiple structured stakeholder interviews. The process flowchart was evaluated based on stakeholder interviews. Their responses revealed strengths and weaknesses that can be used in future studies. By mapping out the existing legislation-based workflow, this study aims to lay the groundwork for a more efficient, digitised system to manage restoration projects in Turkey. One of the most important findings was that the restoration project submission and evaluation process evolved over the years, and the councils compensated for the insufficient definitions of the related legislation. Under these terms, a common medium is necessary to support our analyses of the need for DSSs. This study is an example of a process surveying explicit processes defined in legislation and tacit, experience based processes.
Keywords: Architecture (Other); Mimarlık (Diğer)